Effects of sown and spontaneous inter-row vegetation on weeds and beneficial arthropods in vineyards - Rocher, Léo; Melloul, Emile; Blight, Olivier; Bischoff, Armin (Basic and applied ecology, 2024)
The intensification of crop management has resulted in a decline of biodiversity in the last decades, in particular through habitat loss, fragmentation and degradation. Semi-natural habitats within agricultural landscapes such as hedges, grasslands or herbaceous field margins, provide resources and refuge to beneficial arthropods. In vineyards, extensively used inter-row vegetation may be functionally equivalent to such semi-natural habitats, and sowing of plant species rich in floral resources may improve habitat functions. In this study, three types of vineyard inter-row vegetation treatments were compared in 15 vineyards of South-eastern France: (1) sowing a high-diversity seed mixture (HD) with a high number of nectariferous plant species, (2) spontaneous vegetation, and (3) tilled inter-rows. We monitored the inter-row vegetation including problematic weeds, the abundance of beneficial arthropods, and the predation of sentinel prey. The invasive weedy grass species Cynodon dactylon showed a lower cover in HD inter-rows than in spontaneous vegetation, whereas no differences were found for the invasive herb Erigeron sumatrensis. Both weed species were still best controlled in tilled inter-rows. Beneficial arthropods were less abundant in tilled than in spontaneously vegetated and sown inter-rows. Day predation was higher in HD inter-rows than in spontaneous vegetation although no significant differences were found for observed predators. Over all treatments, plant species richness, flower and grass cover had a positive influence on several beneficial arthropod groups. Our results highlight the positive effects of species-rich inter-row vegetation on weed control, beneficial arthropod abundance and predation but also showed that further research is needed to improve the efficiency beyond services already provided by spontaneous vegetation.